Virtual Simulation Method in Hospital Design - Amien, Muchammad; Rachmawati, Murni; Faqih, Muhammad (Institut Teknologi Sepuluh Nopember, 2017)
The development of computing technology affords wide opportunities to apply the virtual reality in the building design process. Virtual reality not only promotes possibilities to explore architectural forms but also affords capability to learn the interaction of users and the design object as if they do in the real situation. User reaction toward design model can be learned and used to be effective information to develop a promoted preliminary design. The user satisfaction and suitability are indicated by their feedback of design object in virtual reality simulation. This paper aims to explain the application of the method on hospital building design. In this case the authors found that the method is very accurate to capture the user need and very valuable to support design process.